Cancer, Intimacy and Sexuality : A Practical Approach - Reisman, Yacov; Gianotten, Woet L. (Springer International Publishing : Imprint: Springer, 2017)
This book provides a wide-ranging overview of the sexual consequences of cancer and its treatment with the aim of equipping physicians and other health care providers with the awareness and knowledge required in order to offer patients effective treatment. While sexuality may not be the primary focus for cancer patients, at some point, whether because of sexual changes of relationship issues, many patients come to acknowledge the effects that cancer and its treatment have had on their sexuality. Although the impacts are frequently similar, significant variation is observed. Some patients experience changes in all phases of sexual response, while others experience none; moreover, the consequences of the effects may be felt differently by patients and partners. Unfortunately, many physicians and health care providers remain insufficiently aware of the impact of cancer on sexuality and/or lack knowledge about the concerns of patients and the available treatments and coping strategies. A further issue is the reticence of physicians to discuss sexuality and the fear of sexologists to talk to patients about cancer. Readers will find this book to be a rich source of help in overcoming these constraints and delivering suitable care to patients.
Keywords: Medicine.; Gynecology.; Oncology.; Nursing.; Urology.; elektronické knihy; electronic books